Equine MicroRNAs: Performance, Reproduction, and Disease - Herkenhoff, Marcos Edgar (MicroRNA, 2025)
MicroRNAs (miRNAs) are molecules that regulate gene expression by targeting the 3′ untranslated region (UTR) of mRNAs. They are essential in numerous biological processes like growth, metabolism, and muscle development. miRNA research has become crucial in livestock breeding, offering solutions for improving animal health and productivity. This review focuses on miRNAs' roles in equine performance, reproduction, and disease, highlighting key findings and future applications in these areas. It discusses the use of circulating miRNAs (ci-miRNA) as biomarkers for athletic performance, particularly in endurance sports, by monitoring responses to exercise-induced stress and recovery. It also examines miRNAs involved in reproductive health, such as those influencing endometritis, oocyte maturation, and embryo development. In terms of disease, miRNAs are highlighted as potential biomarkers for osteoarthritis and sarcoids, offering insights into early diagnosis and treatment. Overall, the review emphasizes the promise of miRNAs in improving equine care through personalized diagnostics and therapeutic approaches.
Keywords: reproduction